Bureaucratic Reform and Abuse of Power Implicate Corruption in Public Services: A Philosophical Perspective of Law in the North Halmahera Regency Government - Elstonsius Banjo (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Bureaucratic Reform is a process of restructuring government bureaucracy, encompassing organization, governance, legislation, human resources, supervision, accountability, and public services, as well as the mindset and cultureset (work culture) of the apparatus. In practice, bureaucratic reform has not been optimally implemented, resulting in frequent abuse of power that has implications for corruption. The purpose of this research that is bureaucratic reform to become a necessity and a foundation for the North Halmahera Regency government apparatus, in order to successfully lay the political, legal, and economic foundations for democratic life in Indonesia. The